Respuesta :

the answer would be A. -18x^7

hope this helps:)

Answer:

[tex]-6x^2\left(3x^5\right)=-18x^7[/tex]

Hence, option (A) is true.

Step-by-step explanation:

Given the expression

[tex]-6x^2\left(3x^5\right)[/tex]

[tex]\mathrm{Apply\:exponent\:rule}:\quad \:a^b\cdot \:a^c=a^{b+c}[/tex]

i.e. [tex]x^2x^5=\:x^{2+5} \\[/tex]

so the expression becomes

[tex]-6x^2\left(3x^5\right)=-6\cdot \:\:3x^{2+5}[/tex]

[tex]\mathrm{Add\:the\:numbers:}\:2+5=7[/tex]

                  [tex]=-6\cdot \:3x^7[/tex]

[tex]\mathrm{Multiply\:the\:numbers:}\:6\cdot \:3=18[/tex]

                   [tex]=-18x^7[/tex]

Therefore,

[tex]-6x^2\left(3x^5\right)=-18x^7[/tex]

Hence, option (A) is true.

ACCESS MORE